The Effectiveness of Bocce Games to Improve Social Skills for Mentally Disabled Special Needs Students at Muhammadiyah Sumedang Special Needs School - Fitri, Shafira Nabila (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
As living creatures, they cannot essentially live alone, they need to socialize with each other, interactions between individuals and individuals, individuals with groups, and groups with groups. However, some parties feel that they need a longer process, which is different from others, both naturally and empirically. Therefore, there are quite a few things that can trigger the interaction process to develop as it should, one of which is games. The game of bocce is very close to our brothers and sisters who have intellectual disabilities, both cognitive, affective, and psychomotor, who can be oriented to the presence of bocce. If the needs of social norms are not met, at least by people with mental retardation, it is feared that these ABK will not reconcile themselves and will continue to feel ostracized. This research is important to research to embrace again so that a feeling of equality arises even though they are different and to provide an effective game so that the social skills of children with special needs who are mentally retarded can emerge at least in the surrounding environment.